**Example 1**:

Form a quadratic expression by multiplying each of the following.

(a) (6

*p*– 2)(2*p*– 1)(b) (

*m*+ 5)(4 – 7*m*)(c) (

*x*+ 2) (2*x*– 3)

Solution:Solution:

*p*– 2)(2

*p*– 1)

= (6

*p*)(2*p*) + (6*p*)(-1) + (-2)(2*p*) +(-2)(-1)= 12

*p*^{2}– 6*p*– 4*p*+ 2= 12

*p*^{2}– 10*p*+ 2(b) (

*m*+ 5)(4 – 7

*m*)

= (

*m*)(4) + (*m*)(-7*m*) + (5)(4) + (5)(-7*m*)= 4

*m*– 7*m*^{2}+ 20 – 35*m*= – 7

*m*^{2}– 31*m*+ 20(c) (

*x*+ 2) (2

*x*– 3)

= (

*x*)(2*x*) + (*x*)(-3) + (2)(2*x*) + (2)(-3)= 2

*x*^{2}-3*x*+ 4*x*– 6= 2

*x*^{2}+*x*– 6